Data Governance Strategy for E-Government in Bandung District Governments - Nindito Prasetyo, Hanung; Fajar Surya Gumilang, Soni (International Journal of Engineering and Technology, 2019)
The era of information technology has a tremendous impact for the government in providing a variety of services both internally and externally through the data and information generated. But in some ways, Bandung district governments faced with data and information that are inadequate or not fully trustworthy, or the amount of data that is so great that it is often difficult to get reliable analysis results. In the fast-paced era of government-led course requires accurate data and information. If the Bandung district administration with different levels of the units do not have good data quality will certainly complicate the lead in obtaining the information needed in decision-making. Therefore, the government of Bandung district need to design data governance strategy and information in the system of government so that a system built able to answer the public demand for transparency of government activities and government's own internal needs, especially in terms of helping decision-making Bandung district government. this research use qualitative analysis with case study and focus produce data governance srategy model for E-government.Â